Graphene transfer process based on gels. - Neuvonen, Santeri (2023)
In this thesis, we suggest an alternative approach to graphene transfer by using gel materials as a support layer. The literature section focuses on graphene and its properties to find the optimal gel for the graphene transfer process. The experimental section focuses on establishing a working gel transfer for the graphene by experimenting with hyaluronic acid, N-fluorenylmethoxycarbonyl phenylalanine (Fmoc-F) and dipeptide tert-butyloxycarbonyl diphenylalanine tert butyl ester (BocFFOtBu) gels.